Preparation method of alloy target material
By using adsorbent sheets and hydrogen storage materials to assist in sintering, the problems of purity, density and uniformity in the preparation of alloy targets were solved, and high-purity, high-density alloy targets were prepared, which are suitable for large-scale industrial production.
Patent Information
- Application Number
- CN202511411200.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-29
- Publication Date
- 2025-11-04
- Estimated Expiration
- 2045-09-29
AI Technical Summary
Existing alloy sputtering methods struggle to achieve ultra-high purity, high density, and uniformity of composition and microstructure, leading to reliance on imports for domestically produced alloy sputtering materials in high-end applications.
Adsorbent sheets and/or hydrogen storage materials are used to assist sintering. The adsorbent sheets absorb impurities in the sintering environment, and the hydrogen storage materials release hydrogen to consume oxygen impurities, promoting the discharge of gas from the pores and the migration and shrinkage of materials, thereby improving the purity and density of the alloy target material.
It significantly improves the purity, density, and microstructure uniformity of alloy targets, reduces oxygen content, and is suitable for large-scale industrial production, avoiding the high cost and high risk of using a dedicated hydrogen sintering furnace.
Smart Images

Figure CN120888882A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of target material preparation, and particularly relates to a preparation method of an alloy target material. BACKGROUND
[0002] As the core material of vacuum coating technology, the purity, density and composition uniformity of the alloy target material directly affect the film performance and further affect the quality of the terminal product. Common preparation methods of the alloy target material mainly include a melting and casting method and a powder metallurgy method. The melting and casting method is to form an alloy melt by vacuum melting of metal raw materials with a certain ratio, then pour into a mold for forming, and then form an alloy target material through mechanical processing or subsequent deformation treatment. However, the molten liquid is easy to produce bubbles during pouring, and for multi-element metal components with large difference in melting point and density, segregation is also easy to occur, thereby affecting the density, composition and uniformity of the alloy target material. The powder metallurgy method is to form a target blank by pressing and sintering of metal powder raw materials with a certain ratio, and then mechanically processing to form an alloy target material. However, impurities such as oxygen and nitrogen are easy to be introduced during powder processing and sintering, thereby affecting the purity of the composition of the alloy target material. The insufficient purity has become a key bottleneck for the application of domestic alloy target materials in core industries such as advanced semiconductors and display panels, resulting in a high dependence on imports of domestic ultra-high purity alloy target materials in high-end application fields.
[0003] Therefore, the existing preparation method of the alloy target material cannot simultaneously consider the problems of ultra-high purity, high density, composition and uniformity. SUMMARY
[0004] The application aims to provide a preparation method of an alloy target material, and aims to solve the technical problem that the existing preparation method of the alloy target material cannot simultaneously consider ultra-high purity, high density, composition and uniformity.
[0005] To achieve the above application purposes, the technical scheme adopted by the application is as follows: The application provides a preparation method of an alloy target material, comprising the following steps: providing a target alloy powder; isostatic pressing the target alloy powder to form a green compact; surrounding the adsorbent sheet and / or hydrogen storage material around the four sides of the green compact, and then performing a first sintering treatment to obtain an alloy target material.
[0006] Compared with the prior art, the application has the following beneficial effects: The preparation method of the alloy target provided by the application adopts adsorbent sheet and / or hydrogen storage material to assist sintering, the adsorbent sheet can absorb O2, N2, CO2 and other impurities in the sintering environment, effectively promote the rapid discharge of gas in the pores of the sintered body, promote the shrinkage of the material, thereby greatly reducing the pores and defects, improving the purity, density, composition and uniformity of the alloy target, and solving the problem that the residual pores are formed due to the failure of the gas in the pores to diffuse in time in the traditional sintering, thereby hindering the shrinkage of the sintered body. The hydrogen storage material releases hydrogen gas to consume O2 in the sintering environment during the sintering process, effectively inhibits oxygen impurities, and also reduces the metal oxides of the sintered body to generate water vapor, thereby greatly reducing the oxygen content of the alloy target, improving the purity of the alloy target, and solving the problem that the conventional sintering furnace cannot directly sinter with hydrogen. In addition, the preparation method has no special requirements for the sintering equipment, is low in cost, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF DRAWINGS
[0007] In order to more clearly illustrate the technical solutions in the embodiments of the application, the drawings needed to be used in the embodiments or prior art description will be briefly introduced. Obviously, the drawings in the following description are only some embodiments of the application, and other drawings can be obtained by those skilled in the art without creative labor.
[0008] Figure 1 is a flow chart of the preparation method of the alloy target provided by the embodiments of the application; Figure 2 is a cross-sectional view of the hydrogen storage material used in the preparation method of the alloy target provided by the embodiments of the application.
[0009] In the drawings, various reference signs represent: 1 - slow-release shell, 2 - hydrogen storage alloy powder. DETAILED DESCRIPTION
[0010] In order to make the technical problems, technical solutions and beneficial effects to be solved by the application more clearly understood, the application will be further described in detail below with reference to the embodiments. It should be understood that the specific embodiments described herein are only used to explain the application and not to limit the application.
[0011] In the target sintering process, if hydrogen is to be introduced, special requirements are placed on the equipment. A conventional vacuum sintering furnace cannot be directly used for hydrogen sintering, and a special hydrogen sintering furnace must be used, and the furnace must at least meet the following requirements: (1) explosion-proof sealing: the furnace body must be designed with full sealing to prevent hydrogen leakage from causing an explosion; (2) equipped with a high-precision atmosphere control system and multiple safety systems: high-purity hydrogen needs to be introduced, and the air in the furnace must be completely evacuated before hydrogen is introduced, and a nitrogen replacement channel, a high-precision flow control system, a safety monitoring system such as a leakage alarm system, and a water cooling protection system need to be installed to automatically cut off the gas source and power supply in the event of a leak, and to prevent the high-temperature failure of the sealing ring; (3) the heating element needs to be resistant to hydrogen embrittlement: conventional resistance wires are prone to hydrogen embrittlement, and need to be replaced with hydrogen-resistant materials such as molybdenum and tungsten. As can be seen, the internal structure of a sintering furnace that can meet the hydrogen sintering requirements is extremely complex, not only is the cost high, but also the maintenance frequency is high and the operation is complex, and a dedicated person is needed to maintain it; in addition, it has a high risk of flammability and explosiveness. Therefore, the present application uses hydrogen storage materials to assist sintering, which can safely and conveniently provide a controllable reducing environment without introducing impurities into the target, significantly improving the oxygen content and density of the alloy target and other properties. The problem of conventional vacuum sintering furnaces being unable to sinter with hydrogen is solved, avoiding the high cost, difficult maintenance, and high risk of using a special hydrogen sintering furnace, and also solving the problem of hydrogen sintering furnaces not being suitable for the preparation of medium- and low-value target materials.
[0012] The present application provides a preparation method of an alloy target material, as shown in Figure 1 The present application provides a preparation method of an alloy target material, as shown in S01: providing a target alloy powder; S02: isostatic pressing the target alloy powder to form a green body; S03: surrounding the adsorbent sheet and / or hydrogen storage material around the green body, and then performing a first sintering treatment to obtain an alloy target material.
[0013] The preparation method of the alloy target material provided by the present application uses an adsorbent sheet and / or hydrogen storage material to assist sintering. The adsorbent sheet can absorb O2, N2, CO2, and other impurities in the sintering environment, effectively promoting the rapid discharge of gas in the pores of the sintered body, promoting the shrinkage of the material, thereby greatly reducing the pores and defects, improving the purity, density, composition, and uniformity of the alloy target material, and solving the problem of residual pores formed by the inability of the gas in the pores to diffuse in time during traditional sintering, which hinders the shrinkage of the sintered body. The hydrogen storage material releases hydrogen gas to consume O2 in the sintering environment during sintering, effectively inhibiting oxygen impurities, and can also reduce metal oxides in the sintered body to generate water vapor, thereby greatly reducing the oxygen content of the alloy target material, improving the purity of the alloy target material, and solving the problem of conventional sintering furnaces being unable to directly sinter with hydrogen. In addition, the preparation method has no special requirements for the sintering equipment, has low cost, and is suitable for large-scale industrial production.
[0014] The step S01 above, in the embodiment, the target alloy powder includes any one of zinc telluride alloy powder, aluminum scandium alloy powder, copper gallium alloy powder, molybdenum niobium alloy powder, molybdenum tungsten alloy powder, neodymium iron boron alloy powder. These target alloy powders of the embodiment can be obtained by purchasing, of course, can be prepared according to the technology, conditions and so on described in the literature or books, the purity of the target alloy powder is required to be ≥ 99.99%, and the particle size is 10-50 μm.
[0015] The step S02 above, in the embodiment, the step of isostatic pressing the target alloy powder includes: filling the target alloy powder into the mold, and then performing cold isostatic pressing forming treatment under a pressure of 200-300 MPa, and pressure maintaining for 0.5-2 h.
[0016] The step S03 above, in the embodiment, the distance between the adsorbent sheet and the green body is ≥ 0.1 cm, or the distance between the hydrogen storage material and the green body is ≥ 0.1 cm. The distance range can not only ensure that the impurities such as oxygen and nitrogen around the green body are quickly adsorbed by the adsorbent sheet or the hydrogen released by the hydrogen storage material is quickly consumed, but also can avoid contact with the green body to prevent the sintered body from being adhered and new impurities from being introduced.
[0017] In the embodiment, the thickness of the adsorbent sheet is 0.05-0.5 cm.
[0018] In the embodiment, the adsorbent sheet is selected from a zirconium-based alloy or a titanium-based alloy.
[0019] In the embodiment, the zirconium-based alloy includes Zr and M1 in a mass ratio of (70-90):(10-30), and M1 is selected from one or more combinations of Ti, V, Al, Fe, Co, La, Ce, Pr, Nd, Y. The zirconium-based alloy with these components has high chemical affinity to O, N, H, C, etc., and can still continuously absorb at 500-1400 ℃, which can greatly reduce the oxygen content, nitrogen content, etc. of the target material. And the multi-element solid solution alloy can improve the stability of the oxidation-resistant film, avoid passivation failure, and effectively prolong the service life of the zirconium-based alloy adsorption.
[0020] In the embodiment, the titanium-based alloy includes Ti and M2 in a mass ratio of (60-90):(10-40), and M2 is selected from one or more combinations of Zr, Mo, Ni, V, Al, Fe, Mn. The titanium-based alloy with these components has high chemical affinity to O, N, H, C, etc., and can still continuously absorb at 500-1400 ℃, which can greatly reduce the oxygen content, nitrogen content, etc. of the target material. And the multi-element solid solution alloy can improve the stability of the oxidation-resistant film, avoid passivation failure, and effectively prolong the service life of the titanium-based alloy adsorption.
[0021] In the embodiment, as Figure 2As shown, the hydrogen storage material includes a slow-release shell 1 and a hydrogen storage alloy powder 2 filled in the slow-release shell 1, the hydrogen storage alloy powder 2 is used to provide hydrogen release, and the slow-release shell 1 is provided with pores for controlling the hydrogen release rate of the hydrogen storage alloy powder 2.
[0022] In an embodiment, the step of preparing the slow-release shell includes: mixing the slow-release material powder, the pore-forming agent, the binder and ethanol to obtain a slurry; slip casting the slurry to obtain a green body; and performing pre-burning treatment and second sintering treatment on the green body to obtain the slow-release shell.
[0023] In an embodiment, the pore-forming agent is selected from any one of starch, urea, ammonium bicarbonate and polymethyl methacrylate.
[0024] In an embodiment, the pore-forming agent is added in an amount of 1-10% of the mass of the slow-release material powder, and the particle size of the pore-forming agent is 0.5-50 μm. By controlling the amount and particle size of the pore-forming agent, the pore size and porosity range of the slow-release shell can be effectively controlled, so as to ensure that the slow-release shell can accurately control the hydrogen release rate.
[0025] In an embodiment, the pre-burning treatment is performed at a temperature of 300-600 ℃ for 1-4 h, and the second sintering treatment is performed at a temperature of 1500-2400 ℃ for 4-24 h. The pore-forming agent is removed by pre-burning to form pores, and then the density and strength of the slow-release shell are improved by sintering, and pores with a target particle size are formed.
[0026] In an embodiment, the thickness of the slow-release shell is 0.01-0.2 cm, and the pore size of the pores is 0.3-35 μm. The thickness and pore size range of the slow-release shell in the embodiment can ensure that the mechanical strength is sufficient to withstand loading and handling, and at the same time, the pore structure does not collapse at high temperatures, and the slow-release effect is maintained.
[0027] In an embodiment, the porosity is 0.8-8%. The porosity range in the embodiment can accurately control the hydrogen release rate, form a weak reducing sintering environment, consume oxygen in the sintering environment and reduce metal oxides in the sintered body to form water vapor to be discharged, effectively inhibit the oxidation of the alloy target material, and not cause hydrogen embrittlement or bulging, thereby greatly reducing the oxygen content of the alloy target material.
[0028] In an embodiment, the material of the slow-release shell is selected from one or more of molybdenum, tungsten, niobium and tantalum. These metals do not react with hydrogen and do not cause hydrogen embrittlement, and can be repeatedly used. At the same time, these metals have high melting point, specific heat capacity and thermal conductivity, have large heat storage capacity per unit volume, and can quickly and uniformly heat, which can effectively inhibit the fluctuation of the furnace temperature and improve the uniformity of the hearth temperature, thereby further improving the grain uniformity of the target material.
[0029] In an embodiment, the particle size of the hydrogen storage alloy powder is 100-500 μm, which can ensure the filling density and avoid the blockage of the pores of the slow-release shell.
[0030] In the embodiments, the hydrogen storage alloy powder is selected from any one of titanium-based hydrogen storage alloy powder, zirconium-based hydrogen storage alloy powder, and vanadium-based hydrogen storage alloy powder.
[0031] In the embodiments, the titanium-based hydrogen storage alloy powder includes Ti and M3, where M3 is selected from one or more combinations of Fe, Mn, Cr, Zr, and V; for example, the titanium-based hydrogen storage alloy powder can be TiFe, Ti 0.8 Zr 0.2 Mn 2-x Cr x (x = 0.2, 0.4, 0.6, 0.8, and 1.0), T i0.9 Zr 0.2 Mn 1.8 V 0.2 Ti 0.9 Zr x Mn 1.8-y Cr y V 0.2 (x=0.1, 0.15 and 0.2; y=0.2 and 0.4) etc.
[0032] In the embodiments, the zirconium-based hydrogen storage alloy powder includes Zr and M4, where M4 is selected from one or more combinations of V, Cr, Mn, Ni, Fe, and Ti; for example, the zirconium-based hydrogen storage alloy powder can be ZrV2, ZrCr2, ZrMn2, or Zr 0.8 Ti 0.2 Mn 0.44 Cr 0.11 V 0.44 Ni 1.32 wait.
[0033] In the embodiments, the vanadium-based hydrogen storage alloy powder includes V and M5, where M5 is selected from one or more combinations of Ti, Zr, Cr, Fe, Mn, and Ni; for example, the vanadium-based hydrogen storage alloy powder can be V. 0.3 Ti 0.35 Cr 0.25 Fe 0.1 V 0.7 Zr 0.1 Ni 0.2 wait.
[0034] In this embodiment, before injecting the hydrogen storage alloy powder into the slow-release shell, the process further includes pretreatment, activation, and hydrogen absorption treatment. Specifically, the pretreatment step may include: placing the hydrogen storage alloy powder in a hydrogen absorption reactor, evacuating it to below 0.1 Pa, and then heating it to 100-150°C to remove surface-adsorbed impurities such as H2O, CO2, and O2. The activation treatment step may include: evacuating the hydrogen absorption reactor to 10... -2After the pressure is reduced to 10 Pa, the temperature is raised to 50-100℃, then hydrogen gas with a purity of 99.99% is introduced to make the pressure of the hydrogen absorption reactor 1-5 MPa, and the pressure is maintained for 0.5-2 h before the valve is closed to stop hydrogen absorption. Of course, the steps of pretreatment, activation and hydrogen absorption treatment can also be pretreated, activated and hydrogen absorption treated according to the actual material of the hydrogen storage alloy powder, and the techniques, conditions, etc. described in the literature or books in the art. -2 After the pressure is reduced to 10 Pa, the temperature is raised to 50-100℃, then hydrogen gas with a purity of 99.99% is introduced to make the pressure of the hydrogen absorption reactor 1-5 MPa, and the pressure is maintained for 0.5-2 h before the valve is closed to stop hydrogen absorption. Of course, the steps of pretreatment, activation and hydrogen absorption treatment can also be pretreated, activated and hydrogen absorption treated according to the actual material of the hydrogen storage alloy powder, and the techniques, conditions, etc. described in the literature or books in the art.
[0035] In the embodiment, the vacuum degree of the first sintering treatment is 10 -2 ~10 -3 Pa, the temperature is 500-1400℃, and the time is 4-24 h.
[0036] The embodiment of the present application uses adsorbent sheets and hydrogen storage materials to assist sintering, effectively improving the purity, density, composition and uniformity of the alloy target material, and the hydrogen storage material can also be reused. When the hydrogen release of the hydrogen storage alloy powder of the hydrogen storage material is complete, the hydrogen storage alloy powder can be taken out to be re-hydrogenated and then injected into the slow-release shell, thereby realizing recycling and reducing costs.
[0037] The following will be described in conjunction with specific embodiments.
[0038] Embodiment 1 The embodiment provides a preparation method of a zinc telluride target material, comprising the following steps: S11: purchasing zinc telluride powder with a purity of ≥99.99% and a particle size of 10-50 μm; S12: forming treatment: filling the zinc telluride powder into a mold, and performing cold isostatic pressing forming treatment under a pressure of 250 MPa, and maintaining the pressure for 1 h to form a green body; S13: preparing a hydrogen storage material: The molybdenum powder (particle size 2-15 μm), starch (particle size 5-30 μm), polyvinyl alcohol and ethanol are ball milled and mixed to obtain a slurry; the slurry is loaded into a vacuum tank, vacuum degassing is performed, and then the slurry is injected into a sealed graphite mold cavity at a pressure of 1 MPa until no water droplets come out of the mold, the mold is opened, the solidified green body is taken out, and the green body is placed at room temperature for 24 h to obtain a green body; the green body is placed in a vacuum sintering furnace, vacuum is drawn to 5×10 -2Pa, and then is heated to 400 DEG C to perform a pre-sintering treatment for 2h, and then is heated from 400 DEG C to 2100 DEG C to perform a second sintering treatment for 18h, to obtain the slow-release shell; wherein the adding amount of the starch is 5% of the mass of the molybdenum powder, and the adding amount of the polyvinyl alcohol is 0.5% of the mass of the molybdenum powder; The purchased ferrotitanium alloy powder is placed in the hydrogen absorption reaction kettle, vacuumed to below 0.1 Pa, and heated to 130 DEG C for 1h; the hydrogen absorption reaction kettle is vacuumed to 10 -2 Pa, and then is heated to 300 DEG C, and then hydrogen (with a purity of 99.99%) is introduced to make the pressure of the hydrogen absorption reaction kettle be 2MPa, and is kept for 1h; then is heated to 500 DEG C, and the hydrogen is released by reducing the pressure; the hydrogen absorption-hydrogen release process is repeated for 3 times; the hydrogen absorption reaction kettle is vacuumed to 10 -2 Pa, and then is heated to 75 DEG C, and then hydrogen (with a purity of 99.99%) is introduced to make the pressure of the hydrogen absorption reaction kettle be 3MPa, and is kept for 1h, and then the valve is closed to stop the hydrogen absorption, to obtain the hydrogen-filled ferrotitanium hydrogen storage alloy powder; The ferrotitanium hydrogen storage alloy powder is injected into the slow-release shell, and then the slow-release shell is sealed by welding, to obtain the hydrogen storage material; It is detected that the porosity of the slow-release shell is 3.5%, and the pore size is 4.1-25μm; S14: the green body is placed in the vacuum sintering furnace, the adsorbent sheet and the hydrogen storage material are surrounded around the four sides of the green body, and vacuumizing is started to 5*10 -2 Pa, and then is heated to 950 DEG C and is kept for 12h, to obtain the zinc telluride target material; wherein the thickness of the adsorbent sheet is 0.2cm, the material is a zirconium-based alloy with a mass ratio of Zr, Co and Ce being 75:23:2, the distance between the adsorbent sheet and the green body is 0.2cm, and the distance between the hydrogen storage material and the green body is 0.5cm.
[0039] Example 2 The embodiment provides a preparation method of a zinc telluride target material, which is different from the embodiment 1 in that only the adsorbent sheet is used to surround the four sides of the green body, i.e., step S13 is not contained; and step S14 is that the green body is placed in the vacuum sintering furnace, the adsorbent sheet is surrounded around the four sides of the green body, and vacuumizing is started to 5*10 -2 Pa, and then is heated to 950 DEG C and is kept for 12h, to obtain the zinc telluride target material; wherein the thickness of the adsorbent sheet is 0.2cm, the material is a zirconium-based alloy with a mass ratio of Zr, Co and Ce being 75:23:2, and the distance between the adsorbent sheet and the green body is 0.2cm.
[0040] Example 3 The embodiment provides a preparation method of a zinc telluride target material, and the difference from the embodiment 1 is that only a hydrogen storage material is used to surround the green body. -2 Pa below, and then the temperature is increased to 950 DEG C, and the temperature is kept for 12 hours, so that the zinc telluride target material is obtained; wherein the distance between the hydrogen storage material and the green body is 0.5 cm.
[0041] Embodiment 4 The embodiment provides a preparation method of a zinc telluride target material, and the difference from the embodiment 1 is that: Step S11 is that the zinc telluride powder is replaced by aluminum-scandium alloy powder.
[0042] Embodiment 5 The embodiment provides a preparation method of a zinc telluride target material, and the difference from the embodiment 1 is that: Step S11 is that the zinc telluride powder is replaced by copper-gallium alloy powder.
[0043] Embodiment 6 The embodiment provides a preparation method of a zinc telluride target material, and the difference from the embodiment 1 is that: Step S11 is that the zinc telluride powder is replaced by nickel-vanadium alloy powder.
[0044] Embodiment 7 The embodiment provides a preparation method of a zinc telluride target material, and the difference from the embodiment 1 is that: Step S13 is that the titanium-iron alloy powder is replaced by ZrV2 alloy powder, and the titanium-iron hydrogen storage alloy powder is replaced by ZrV2 hydrogen storage alloy powder.
[0045] Comparative example 1 The comparative example provides a preparation method of a zinc telluride target material, and the method comprises the following steps. S1: purchasing zinc telluride powder with purity greater than or equal to 99.99% and particle size of 10-50 microns; S2: forming treatment: the zinc telluride powder is filled into a mold, cold isostatic pressing forming treatment is carried out under the pressure of 250 MPa, pressure is kept for 1 hour, and a green body is formed; S3: sintering treatment: the green body is placed in a vacuum sintering furnace, vacuum is started to be drawn to 5*10 -2 Pa below, and then the temperature is increased to 950 DEG C, and the temperature is kept for 12 hours, so that the zinc telluride target material is obtained.
[0046] Related performance test analysis: 1. The O and N contents in each target material prepared in Examples 1-7 and Comparative Example 1 were tested by an oxygen-nitrogen analyzer, wherein the O content in the zinc telluride powder was <24 ppm, the N content was <12 ppm; the O content in the aluminum scandium alloy powder was <26 ppm, the N content was <11 ppm; the O content in the copper gallium alloy powder was <25 ppm, the N content was <10 ppm; the O content in the nickel vanadium alloy powder was <27 ppm, the N content was <13 ppm.
[0047] 3. After the target materials prepared in Examples 1-7 and Comparative Example 1 were plastic encapsulated, the actual densities of the target materials were tested by an Archimedes method, and the relative densities were calculated based on the theoretical densities by the formula: relative density = actual density / theoretical density x 100%. The test results are shown in Table 1 below. Table 1
[0048] As shown in Table 1, the densities of the target materials prepared in Examples 1-7 were significantly higher than that of Comparative Example 1, and the O, N and total impurity contents of the target materials prepared in Examples 1-7 were significantly lower than those of Comparative Example 1, which indicated that the adsorbent sheet and / or the hydrogen storage material were used to assist sintering in the examples of the present application, the adsorbent sheet could absorb O2, N2, CO2 and other impurities in the sintering environment, promote the rapid discharge of gas in the pores of the sintered body, and promote the migration and shrinkage of the material, thereby greatly reducing the pores and defects, and improving the density and purity of the alloy target material. The hydrogen storage material released hydrogen gas to consume O2 in the sintering environment during the sintering process, effectively inhibited the oxygen impurities, and also reduced the metal oxides in the sintered body to generate water vapor, thereby reducing the oxygen content of the alloy target material.
[0049] The density of the target material prepared in Example 1 was significantly higher than that of Examples 2-3, and the O, N and total impurity contents of the target material prepared in Example 1 were significantly lower than those of Examples 2-3, which indicated that the adsorbent sheet and the hydrogen storage material were used to assist sintering in the examples of the present application, the adsorbent sheet absorbed O2, N2, CO2 and other impurities in the sintered body and the sintering environment, and the hydrogen storage material consumed O2 in the sintering environment to inhibit the oxygen impurities, and reduced the metal oxides to generate water vapor, thereby reducing the oxygen content of the alloy target material, and therefore, the purity and density of the target material could be further improved under the synergistic effect of the two.
[0050] The above only describes the preferred embodiments of the present application and is not intended to limit the present application, and any modifications, equivalent replacements and improvements made within the spirit and principles of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing an alloy target, characterized in that, Includes the following steps: Provide target alloy powder; The target alloy powder is isostatically pressed to form a blank; The adsorbent sheet and / or hydrogen storage material are surrounded around the blank, and then a first sintering treatment is performed to obtain the alloy target.
2. The preparation method according to claim 1, characterized in that, The distance between the adsorbent sheet and the blank is ≥0.1cm, or the distance between the hydrogen storage material and the blank is ≥0.1cm.
3. The preparation method according to claim 1, characterized in that, The thickness of the adsorbent sheet is 0.05~0.5cm; And / or, the adsorbent sheet is selected from zirconium-based alloys or titanium-based alloys.
4. The preparation method according to claim 3, characterized in that, The zirconium-based alloy comprises Zr and M1 in a mass ratio of (70~90):(10~30), wherein M1 is selected from one or more of Ti, V, Al, Fe, Co, La, Ce, Pr, Nd, and Y; Alternatively, the titanium-based alloy comprises Ti and M2 in a mass ratio of (60~90):(10~40), wherein M2 is selected from one or more of Zr, Mo, Ni, V, Al, Fe, and Mn.
5. The preparation method according to claim 1, characterized in that, The hydrogen storage material includes a slow-release shell and hydrogen storage alloy powder filled in the slow-release shell. The hydrogen storage alloy powder is used to provide hydrogen release. The slow-release shell has pores to control the hydrogen release rate of the hydrogen storage alloy powder.
6. The preparation method according to claim 5, characterized in that, At least one of the following conditions must be met: The thickness of the sustained-release shell is 0.01~0.2cm; The pore size is 0.3~35μm; The porosity of the sustained-release shell is 0.8-8%; The material of the sustained-release shell is selected from one or more of molybdenum, tungsten, niobium, and tantalum; The particle size of the hydrogen storage alloy powder is 100~500μm; The hydrogen storage alloy powder is selected from any one of titanium-based hydrogen storage alloy powder, zirconium-based hydrogen storage alloy powder, and vanadium-based hydrogen storage alloy powder.
7. The preparation method according to claim 6, characterized in that, The titanium-based hydrogen storage alloy powder includes Ti and M3, wherein M3 is selected from one or more combinations of Fe, Mn, Cr, Zr, and V; And / or, the zirconium-based hydrogen storage alloy powder comprises Zr and M4, wherein M4 is selected from one or more combinations of V, Cr, Mn, Ni, Fe, and Ti; And / or, the vanadium-based hydrogen storage alloy powder comprises V and M5, wherein M5 is selected from one or more combinations of Ti, Zr, Cr, Fe, Mn, and Ni.
8. The preparation method according to claim 5, characterized in that, The steps for preparing the sustained-release shell include: The slow-release material powder, pore-forming agent, binder and ethanol are mixed to obtain a slurry; The slurry is poured into molds to obtain a blank; The blank is subjected to pre-firing and second sintering treatments to obtain a slow-release shell.
9. The preparation method according to claim 8, characterized in that, At least one of the following conditions must be met: The pore-forming agent is selected from any one of starch, urea, ammonium bicarbonate, and polymethyl methacrylate; The amount of the pore-forming agent added is 1-10% of the mass of the slow-release material powder; The particle size of the pore-forming agent is 0.5~50μm; The pre-firing treatment is carried out at a temperature of 300~600℃ for 1~4 hours; The second sintering treatment is performed at a temperature of 1500~2400℃ for 4~24 hours.
10. The preparation method according to any one of claims 1 to 9, characterized in that, At least one of the following conditions must be met: The vacuum degree of the first sintering process is 10. -2 ~10 -3 Pa, temperature 500~1400℃, time 4~24h; The purity of the target alloy powder is ≥99.99%, and the particle size is 10~50μm; The target alloy powder includes any one of zinc telluride alloy powder, aluminum scandium alloy powder, copper gallium alloy powder, molybdenum niobium alloy powder, molybdenum tungsten alloy powder, and neodymium iron boron alloy powder.
Citation Information
Patent Citations
Low-oxygen-content alloy target material and preparation method thereof
CN118064847A
Preparation method of silicon-molybdenum alloy target material
CN119703080A
Hydrogen absorbing composite
JP2003286508A
Method for producing zinc oxide-based sintered compact, and target
JP2013209741A